Chemically Responsive Elastomers Exhibiting Unity‐Order Refractive Index Modulation. Issue 7 (8th January 2018) - Wu, Di M.; Solomon, Michelle L.; Naik, Gururaj V.; García‐Etxarri, Aitzol; Lawrence, Mark; Salleo, Alberto; Dionne, Jennifer A.
Abstract: Chameleons are masters of light, expertly changing their color, pattern, and reflectivity in response to their environment. Engineered materials that share this tunability can be transformative, enabling active camouflage, tunable holograms, and novel colorimetric medical sensors. While progress has been made in creating artificial chameleon skin, existing schemes often require external power, are not continuously tunable, and may prove too stiff or bulky for applications. Here, a chemically tunable, large‐area metamaterial is demonstrated that accesses a wide range of colors and refractive indices. An ordered monolayer of nanoresonators is fabricated, then its optical response is dynamically tuned by infiltrating its polymer substrate with solvents. The material shows a strong magnetic response with a dependence on resonator spacing that leads to a highly tunable effective permittivity, permeability, and refractive index spanning negative and positive values. The unity‐order index tuning exceeds that of traditional electro‐optic and photochromic materials and is robust to cycling, providing a path toward programmable optical elements and responsive light routing. Abstract : Engineered materials with large refractive index tunability can be transformative, enabling active camouflage, tunable holograms, and novel colorimetric medical sensors. A chemically tunable, large‐area metamaterial that accesses a wide range of colors and refractive indices through solvent infiltration is reported. The unity‐order index tuning is much larger than traditional dynamic materials and is robust to cycling.